2014
DOI: 10.1590/2237-6089-2014-0004
|View full text |Cite
|
Sign up to set email alerts
|

Emotional dimensions in people with aggressive behavior: differential responses to affective visual stimuli

Abstract: Introduction: The emotional interaction between personal attributes and the environment is a key element to understand aggression. This study identified emotional responses of people with different aggressive traits to pictures with a specific affective content. Methods: Three hundred fifteen individuals were divided into five groups according to their scores on the Buss-Perry Aggression Questionnaire, which consists of 24 pictures of the International Affective Picture System that depict aggression, the suffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
2
0
2
Order By: Relevance
“…En Latinoamérica se han desarrollado estudios evaluando el iaPs en México (Chayo-Dichy, Velez, Arias, Castillo-Parra, & Ostrosky-Solis, 2003), Colombia (Gantiva et al, 2014;Gantiva, Guerra, & Vila, 2011) y Chile (Dufey, Fernández, & Mayol, 2011;Silva, 2011), los resultados de todas estas investigaciones muestran que los estímulos visuales del iaPs generan estados emocionales similares (altas correlaciones en todas las dimensiones entre las poblaciones), que la valencia es la dimensión sobre la cual se estructuran el resto de dimensiones y que los estímulos pueden ser usados de forma confiable para el estudio de la emoción y la motivación.…”
Section: Introductionunclassified
“…En Latinoamérica se han desarrollado estudios evaluando el iaPs en México (Chayo-Dichy, Velez, Arias, Castillo-Parra, & Ostrosky-Solis, 2003), Colombia (Gantiva et al, 2014;Gantiva, Guerra, & Vila, 2011) y Chile (Dufey, Fernández, & Mayol, 2011;Silva, 2011), los resultados de todas estas investigaciones muestran que los estímulos visuales del iaPs generan estados emocionales similares (altas correlaciones en todas las dimensiones entre las poblaciones), que la valencia es la dimensión sobre la cual se estructuran el resto de dimensiones y que los estímulos pueden ser usados de forma confiable para el estudio de la emoción y la motivación.…”
Section: Introductionunclassified
“…The results showed that people with different aggressive traits, including verbal aggression, valued sexual pictures as more pleasant and exhibited more arousal than people without any aggressive trait. No significant differences were found for the other picture categories (Gantiva et al, 2014). This indicates a relationship between aggression and the emotional response to stimuli with sexual content.…”
Section: Introductionmentioning
confidence: 72%
“…This indicates a relationship between aggression and the emotional response to stimuli with sexual content. Notably, when this same analysis was performed separately for men and women, only women with aggressive traits had a significantly different response to sexual pictures (Gantiva et al, 2014). The latter results are consistent with previous reports in which women and men differed in aggressive behavior (Archer, 2004; Bjorkqvist, Osterman, & Kaukiainen, 1992; Crick & Grotpeter, 1995; Hess & Hagen, 2006; Salmivalli, Kaukiainen, & Lagerspetz, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…También se ha identificado que los puntajes en dominancia varían con respecto al nivel de arousal, siendo menor ante estímulos con valencia aversiva y alto arousal (Gantiva, Rodríguez, Arias, & Rubio, 2012). Bajo esta metodología, se han estudiado fenómenos tan relevantes como las adicciones (Gantiva, Delgado, & Romo-González, 2015;Muñoz et al, 2013), la agresividad (Gantiva et al, 2014) y los trastornos de la conducta alimenticia (Micoli et al, 2014), entre otros. Los resultados de todos los estudios reflejan la eficiencia de esta metodología para la comprensión de las emociones y la motivación en estas problemáticas; sin embargo, aunque Carlos Gantiva, María Casas, Yeraldín Ballén, ET AL. ABSTRACT Conventional tools for the assessment of psychological processes rely on the use of self-report questionnaires and b ehavioral tasks, in spite of the existence of objective and more accurate physiological responses that could provide new insights into such processes.…”
unclassified